Phytofabrication of Magnetite Nanoparticles from Piper betle (L.) var. Mysore and Evaluation of Anti-Breast Cancer Potentials - Shekhar, Ravikant; Prakash, Harischandra Sripathy; Geetha, Nagaraja (Indian Journal of Pharmaceutical Education and Research)
Background: Breast cancer is a predominant disease around the world, with early diagnosis aiding in reducing the spread and recurrence. Plant-mediated nanoparticles have shown promising results in treatment. The current study aimed to synthesize Magnetite Nanoparticles (MNPs) utilizing Piper betle var. Mysuru extract and evaluate its anti-breast cancer potentials. Materials and Methods: The green synthesis included Fe3+ and Fe2+ in a 2:1 proportion, with crude ethyl acetate extract as a reducing, stabilizing, capping, and tailing agent. The MNPs were characterized utilizing UV-vis spectrometry, SEM, EDX, XRD, FTIR, and DLS for various properties like size, crystal structures, presence of functional groups, surface topologies, etc. Results: The diameter of the newly synthesized nanoparticle was 90 nm in diameter, with a face-centered crystal lattice with different phytochemicals like alcohol, phenols, alkanes, etc. The cytotoxicity assay showed IC50 values of Doxorubicin, plant extract, and MNPs to be 16.77±0.56 μg/mL, 26.07±3.14 μg/mL, and 12.35±2.47 μg/mL, respectively. The hemolytic assay showed 8.8% and 12.28% hemolytic activity with plant extract and MNPs, respectively. Conclusion: The MNPs' affordability, Eco-friendliness, and ease of synthesis make them ideal candidates for upscale synthesis to be used as an active drug molecule against breast cancer.
Keywords: Magnetite nanoparticles; Phytofabrication; FTIR; XRD; DLS; MTT assay; Hemolytic Assay